2010
DOI: 10.1007/s10333-010-0225-3
|View full text |Cite
|
Sign up to set email alerts
|

Terraced paddy field rainfall-runoff mechanism and simulation using a revised tank model

Abstract: Terraced paddy fields play important roles in water and soil conservation because their water storage effect reduces and delays flood peaks. This study applies the terraced paddy field rainfall-runoff mechanism to the tank model. Though the traditional four-section tank model can easily simulate rainfall-runoff in a terraced paddy field, it has many parameters that are difficult to calibrate. To address the shortcomings of the traditional four-section tank model, this study develops a revised tank model to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Chang et al (2001) indicated that an excessive number of tanks will only increase the time needed for calculation and the improvement of the simulation results is limited. In fact, a simplified two-layered tank model is also suitable for paddy fields (Chang et al 2001, Chen andYang 2011).…”
Section: Theoretical Analysis Of the Tank Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Chang et al (2001) indicated that an excessive number of tanks will only increase the time needed for calculation and the improvement of the simulation results is limited. In fact, a simplified two-layered tank model is also suitable for paddy fields (Chang et al 2001, Chen andYang 2011).…”
Section: Theoretical Analysis Of the Tank Modelmentioning
confidence: 99%
“…Therefore, several researchers have used the tank model. The runoff-calculation method and characteristics of this model are as follows (Chen and Yang 2011): (a) The model automatically includes the first flush loss and the amount of loss variation during rainfall. They can be determined by the effluent height of the top tank and the infiltration hole.…”
Section: Theoretical Analysis Of the Tank Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that this basin of rice fields is able to provide a accurate simulation and groundwater recharge. Yang and Chen (2010) applied a revised tank model to simulate the rainfall-runoff mechanism in terraced paddy fields, and applied five normal evaluation indexes based on static and hydrological theories to calculate the results. The revised tank model performed more favourably than expected, and precisely predicted the variations and trends in flow discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of representative indexes proved that the revised tank model was an appropriate and valuable tool for simulating rainfall runoff. Nakagiri et al (1999), Lee et al(1996), Yang and Chen (2010), Takeuchi et al (2009) have described the subsurface flow and saturated excess overland flow on the slopes of hills with a soil layer overlaying a relatively impermeable bedrock by applying the kinematic wave model. The runoff, groundwater level, and soil moisture content have been calculated in several rainfall-runoff models by using the kinematic wave approach…”
Section: Introductionmentioning
confidence: 99%